Understanding the Competitive Effects of Blessed Milkthistle Densities on Wheat - REHMAN,A. (2020)
ABSTRACT: Weed-induced yield loss in wheat crop is a great threat to food security in Pakistan. A comprehensive understanding of weed-crop competition is very important to develop sustainable and cost-effective weed management. For this purpose, two-year field studies were conducted to determine the effect of different blessed milkthistle densities on the phenology and yield of wheat crop in a rice-wheat cropping scheme in Sargodha, Pakistan during 2013-2014 and 2014-2015. The experiment comprised seven treatments: control (weed free), weedy check (weedy without any control) and blessed milkthistle densities of 5, 10, 15, 20 and 25 plants m-2. In response to increasing weed density, a gradual reduction in yield and yield-related traits of wheat was noted. Compared to the weed-free control, a significant reduction in number of productive tillers m-2 (20% and 18%), plant height (15% and 18%), spike length (19% and 26%), number of grains spike-1 (23% and 26%), 1000 grain weight (28% and 28%), grain (29% and 30%) and biological (20% and 24%) yields of wheat occurred at and beyond blessed milkthistle density of 5 plants m-2 during 2013-2014 and 2014-2015 respectively. It can be concluded that blessed milkthistle weed must be controlled if its population density reaches 5 plants m-2 in order to avoid significant grain yield losses in wheat.